A polyimide-based nanofiber protective material and preparation method thereof
By preparing polyimide (PI)-based nanofibers, the problems of poor breathability and insufficient mechanical properties of protective clothing materials are solved, and PI-based nanofiber membranes with high breathability, mechanical strength and flame retardancy are achieved, ensuring medical protection The safety and reusability of the service.
Patent Information
- Application Number
- CN202210500368.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-10
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-05-10
AI Technical Summary
The existing protective clothing materials have poor breathability and moisture permeability when providing barrier properties, and the nanofiber materials have insufficient mechanical properties and do not have reuse and flame retardancy, which poses safety risks.
Polyimide (PI)-based nanofibers were prepared by optimizing electrospinning conditions and adding acetone to adjust the fiber diameter, combined with high temperature vapor deposition method, PI-based nanofiber films with high breathability, mechanical properties and flame retardant properties were prepared. , and ensure filtration efficiency and security through physical interception and repeated processing.
It improves the wear comfort and safety of protective clothing, and realizes high breathability, high mechanical strength and high flame retardancy of PI-based nanofiber membranes, ensuring the stability and filtration efficiency of the material after long-term use and reuse.
Smart Images

Figure 220509110354 
Figure 220509110407 
Figure 220509110411
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of protective materials, and specifically relates to a method for preparing a polyimide (PI)-based nanofiber protective material. Background Art
[0002] In the past two decades, the outbreak of infectious diseases has been threatening human life, health and safety. Therefore, the research of effective vaccines and new medical protective clothing for the new coronavirus has become the most urgent scientific research task in the world.
[0003] At present, the mainstream protective clothing materials on the market mainly include polypropylene spunbond / meltblown / spunbond (SMS) nonwoven materials, polyethylene breathable film / nonwoven composite nonwoven materials and polyethylene flash nonwoven materials. These traditional protective clothing can be further divided into two types. The first type provides good barrier properties through a dense material structure, such as polyethylene breathable film / nonwoven composite nonwoven materials and polyethylene flash nonwoven materials. The good barrier properties of this type of material are at the expense of air permeability and moisture permeability, but under long-term working conditions, it will cause serious consequences such as stuffiness, humidity and discomfort in the wearer of the protective clothing. The other type has good air permeability and filtration performance, but its filtration performance is provided by the electrostatic effect, such as SMS nonwoven materials. The electrostatic effect is unstable, and hydrophilic liquids such as ethanol commonly used in medical places can reduce or eliminate the static electricity of the material, and the reduction or elimination of the electrostatic effect will lead to a great reduction in filtration efficiency. Therefore, there are great risks in the use of SMS nonwoven materials.
[0004] With the development of nanotechnology, the emerging nanofiber membrane has high porosity and large specific surface area, and can provide high filtration performance without reducing air permeability and moisture permeability. It is expected to become an ideal alternative material for the next generation of new protective clothing. However, the application of nanofibers in medical protective clothing still faces three major obstacles. The first is that the mechanical properties of nanofibers are poor, which is not conducive to their safety protection in the actual workplace. The second is that nanofiber protective clothing cannot be reused. The regeneration process causes mechanical damage to the nanofibers or the attenuation of electrostatic charges, which will lead to reduced filtration performance. Third, nanofibers are generally not flame retardant, so they cannot protect the safety of medical staff in emergency situations.
[0005] Polyimide (PI) is a unique polymer with excellent mechanical properties, good thermal stability and chemical stability. It has been widely used in aerospace, machinery manufacturing, high-temperature filtration and other fields.
[0006] The present invention prepares a PI-based nanofiber for protective materials, which improves air permeability while ensuring protective performance. First, the electrospinning conditions are optimized in detail, and then acetone is added to the spinning solution to control the diameter and surface smoothness of the nanofibers. Finally, PDMS is deposited on the PI nanofibers by high-temperature vapor deposition. The optimized PI-based nanofiber membrane has good protective performance, chemical stability, mechanical properties and air permeability, which greatly improves the wearing comfort and safety in the workplace. In addition, the optimized PI-based nanofiber membrane mainly relies on physical interception to ensure stability after long-term use and recycling. Therefore, the feasibility of reusing PI-based nanofibers can be achieved through repeated filtration and sterilization. Summary of the invention
[0007] In view of the deficiencies of existing protective materials, the present invention prepares a PI-based nanofiber membrane for medical protective clothing materials.
[0008] An electrospun polyimide (PI)-based nanofiber protective material, the preparation method of which comprises the following steps:
[0009] S1, using N,N-dimethylformamide (DMF) as solvent, dianhydride and diamine monomers were polycondensed to prepare polyamic acid (PAA);
[0010] S2, using the PAA obtained in step S1 as a polymer to prepare a spinning solution, and preparing a PAA nanofiber membrane by electrospinning;
[0011] S3, thermal imidization of the PAA nanofibers obtained in step S2 to prepare a PI nanofiber membrane;
[0012] S4, on the basis of step S1, introducing high volatility solvent acetone into the PAA polymer solvent, adjusting the diameter of the PI nanofiber membrane, and preparing a PI nanofiber membrane with high protection efficiency, high air permeability and high mechanical properties.
[0013] In some embodiments of the present invention, the specific operation of step S1 is: dianhydride monomers and diamine monomers of equal molar mass are polycondensed in DMF at low temperature to form a PAA solution, the polycondensation reaction temperature is -5~0°C, and the reaction time is 10~12 h; the dianhydride monomer is at least one of pyromellitic anhydride (PMDA), biphenyltetracarboxylic anhydride (BPDA), 4,4'-oxydiphthalic anhydride (OPDA), and 4,4'-hexafluoroisopropylidene-phthalic anhydride (6FDA); the diamine is at least one of 4,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), 2,4,6-trimethyl-1,3-phenylenediamine (TMPDA), and 3,5-diaminobenzoic acid (DABA).
[0014] In some embodiments of the present invention, the specific operations of steps S2 and S3 are: the PAA solution is made into a PAA nanofiber membrane by electrospinning technology, and the PAA nanofiber membrane is then subjected to high-temperature imidization to obtain a PI nanofiber membrane. The process conditions of the high-voltage electrospinning are voltage 10-25 KV, receiving distance 13-18 cm, injection speed 0.2-0.8 ml / h; the high-temperature imidization treatment gradient heating process conditions are: under vacuum, 100 ℃ 2 hours, 200 ℃ 2 hours, 300 ℃ 2 hours, heating rate 5 ℃ / min, after stopping heating, slowly cooling to room temperature in a box furnace.
[0015] In some embodiments of the present invention, the concentration of polymer PAA in step S2 is 8~14 wt%; when the PAA concentration is 8wt%, the PI nanofiber membrane is filled with large-sized beads with a diameter of about 1.5μm; when the PAA concentration is 10 wt%, the number of beads in the PI nanofiber membrane begins to decrease, and the nanofibers are arranged more tightly and regularly; when the PAA concentration is 12 wt%, the PI nanofiber membrane is a uniform fiber with a diameter of 200 nm; when the PAA concentration is 14 wt%, the PI nanofiber membrane is alternating thick and thin fibers, with thick fibers of 200 nm and thin fibers of 30~40nm.
[0016] In some embodiments of the present invention, the specific operation of step S4 is: on the basis of a preferred PAA concentration of 12 wt%, a highly volatile solvent acetone is added to the PAA solvent DMF to prepare DMF / acetone mixed solvents of different mass ratios, and the diameter of the PI nanofibers is regulated by changing the amount of acetone added in the solvent to obtain a PI nanofiber membrane with high mechanical properties and high air permeability.
[0017] In some preferred embodiments of the present invention, the method for adjusting the diameter of PI nanofibers, the mass ratio of DMF / acetone in the solvent ranges from 10:0 to 6:4. In some specific embodiments of the present invention, the mass ratio of DMF / acetone in the solvent can be 10:0, 9:1, 8:2, 7:3, 6:4. Preferably, the mass ratio of DMF / acetone in the solvent is 6:4, and the average fiber diameter is 500 nm.
[0018] In some embodiments of the present invention, during the high-temperature imidization process in step S3, a polydimethylsiloxane (PDMS) film is placed in a box furnace together, and PDMS is vapor-deposited on the surface of the PI nanofibers to obtain a highly hydrophobic and highly flame-retardant PI nanofiber membrane.
[0019] In some embodiments of the present invention, the prepared PI nanofiber membrane is placed together with the PDMS film in a closed environment, gradually heated to 250°C, and maintained for 1 hour. The PDMS is decomposed at high temperature and vapor-deposited on the surface of the PI nanofiber during the cooling process, thereby obtaining a highly hydrophobic and highly flame-retardant PI nanofiber membrane.
[0020] In some embodiments of the present invention, the PI nanofiber protective material prepared by the method has high filtration efficiency (>94%), high air permeability (>100 mm / s), high mechanical strength (maximum tensile stress>13 MPa), high hydrophobicity (contact angle>130°) and good flame retardancy.
[0021] In some embodiments of the present invention, the PI nanofiber membrane mainly relies on physical interception, and there is no risk of static elimination leading to a decrease in filtration efficiency. After being treated with alcohol (75%), chlorine-based disinfectant (1%) and ultraviolet irradiation and cycled 5 times, the filtration efficiency and hydrophobicity of the PI nanofiber membrane remain unchanged.
[0022] In some embodiments of the present invention, the prepared PI nanofiber membrane is combined with a substrate by at least one of ultrasound, thermal compounding, and bonding to prepare a reusable medical protective clothing with high air permeability, high mechanical strength, high hydrophobicity, and high flame retardancy.
[0023] The beneficial effects of the present invention are as follows: the PI-based nanofiber membrane prepared by the method of the present invention has excellent properties such as high air permeability, high mechanical strength, high hydrophobicity and good flame retardancy, and while meeting the basic performance of medical protective clothing materials, the air permeability of the material is guaranteed, and the wearing comfort and safety of medical staff are further improved. At the same time, the PI-based nanofiber membrane prepared by the method, after three kinds of disinfection treatments (alcohol, chlorine-based disinfectant, ultraviolet) and 5 cycles, the filtration efficiency and hydrophobicity of the PI-based nanofiber membrane are almost unchanged, proving that the PI-based nanofiber membrane prepared by the method can be used as a reusable medical protective clothing material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 These are electron microscopy images of PI nanofiber membranes with different polymer concentrations in Example 1: (a) 8 wt% (b) 10 wt% (c) 12 wt% (d) 14 wt%.
[0025] Figure 2 This is a diagram of the filtration performance of PI nanofiber membranes with different polymer concentrations in Example 2.
[0026] Figure 3 This is a diagram of the mechanical properties of PI nanofiber membranes with different polymer concentrations in Example 2.
[0027] Figure 4These are electron micrographs of the nanofiber membrane diameter regulated by different ratios of DMF / acetone in Example 3: (a) 10:0 (b) 9:1 (c) 8:2 (d) 7:3 (e) 6:4.
[0028] Figure 5 This is a diagram of the filtration performance of PI nanofiber membranes with different diameters in Example 4.
[0029] Figure 6 This is a diagram of the mechanical properties of PI nanofiber membranes with different diameters in Example 4.
[0030] Figure 7 This is the water contact angle of the PDMS@PI nanofiber membrane in Example 5.
[0031] Figure 8 This is the flame retardancy of pure PI nanofiber membrane and PDMS@PI nanofiber membrane in Example 5.
[0032] Fig. 9 The filtration efficiency of the PI-based nanofiber membrane in Example 6 is shown initially and after 5 cycles of three kinds of disinfection treatments. DETAILED DESCRIPTION
[0033] In order to make the present invention easier to understand, the present invention will be further described in detail below in conjunction with examples, which are merely illustrative and are not intended to limit the scope of application of the present invention. The raw materials or components used in the present invention can be obtained by commercial routes or conventional methods unless otherwise specified.
[0034] Example 1: Preparation of PI nanofiber membranes with different polymer concentrations
[0035] (1) Preparation of spinning solution: First, weigh PMDA and ODA monomers in equal molar ratios and place the chemicals in a vacuum drying oven (120 °C) for 4 h for drying. Then, add ODA to a three-necked flask containing DMF solvent, and stir the flask with a mechanical stirrer until ODA is completely dissolved and the solution is clear and transparent. Subsequently, place the three-necked flask in ice water, wait for the temperature to drop to -5 °C, and then add PDMA in batches. After the addition is completed, react at low temperature for 12 h to obtain a transparent light yellow viscous PAA product with a polymer concentration of ~14 wt%. Dilute the prepared PAA with a polymer concentration of 14 wt% with DMF to prepare spinning solutions with polymer concentrations of 8 wt%, 10 wt% and 12 wt%, respectively.
[0036] (2) Electrospinning: The above spinning solution was transferred into a syringe, and the spinning solution was pushed by a syringe pump. Copper foil was used as the receiving substrate for electrospinning experiments. The spinning solution was controlled to be 0.9 ml, the spinning voltage was 15 KV, the pushing speed was 0.3 ml / h, and the receiving distance was 15 cm.
[0037] (3) Imidization: The PAA nanofiber membrane prepared above was placed in a box furnace for vacuum gradient heating to 100 ℃, 200 ℃ and 300 ℃ respectively. Each temperature gradient was kept for 2 h, and the heating rate was 5 ℃ / min. After the high temperature treatment, the temperature was naturally cooled to finally obtain a PI nanofiber membrane with a polymer concentration of 8 to 14 wt%. The electron microscope image of the PI nanofiber membrane is shown in Figure 1 shown.
[0038] Example 2: Analysis of filtration and mechanical properties of PI nanofiber membranes with different polymer concentrations
[0039] (1) Filtration performance: The filtration performance of the PI nanofiber membranes with different polymer concentrations prepared in Example 1 was analyzed by an automatic filtration tester (TSI Inc., USA, Model 8130) to evaluate the initial filtration efficiency and resistance of the PI nanofiber membranes. Sodium chloride (NaCl) aerosol particles were used as test particles, with an average particle size of about 300 nm (according to the specifications of TSI Inc., the average number median diameter (NMD) and geometric standard deviation (GSD, σg) of NaCl particles were 75 nm and 1.86, respectively). The flow rate was controlled at 32 L / min, corresponding to a face velocity of 5.3 cm / s, and the test area was 100 cm 2 Among them, the 12 wt% PI nanofiber membrane has the best filtration performance, with a filtration efficiency of 99.81%, a resistance of 110.29 Pa, and a quality factor of 0.057 Pa -1 , the results are as follows Figure 2 As shown;
[0040] (2) Mechanical properties: The PI nanofiber membranes with different polymer concentrations prepared in Example 1 were cut into rectangular test strips with a total length of 50 mm and a width of 10 mm using a cutter, and the thickness of the strips was measured using a thickness meter. The thickness of the strips was measured at three points and the average value was taken. The tensile strength of the fiber membrane was measured using a universal material testing machine at a test speed of 10 mm / min. The 12 wt% PI nanofiber membrane had the best filtration performance with a stress of 2.05 MPa. The results are as follows: Figure 3 As shown;
[0041] (3) According to the analysis of the filtration performance and mechanical properties of the PI nanofiber membranes with different polymer concentrations prepared in Example 1, the PI nanofiber membrane with the best comprehensive performance at a polymer concentration of 12 wt% is preferred.
[0042] Example 3: Preparation of PI nanofiber membranes with different diameters
[0043] (1) According to the results of Example 1, a 12 wt% spinning solution is preferred. At the same time, in order to obtain PI nanofibers with different diameters, the PAA spinning solution is prepared with DMF / acetone mixed solvents of different mass ratios. The mass ratios of DMF / acetone are 10:0, 9:1, 8:2, 7:3 and 6:4 respectively;
[0044] (2) The prepared spinning solution was prepared according to steps (2) and (3) in Example 1, and finally PI nanofiber membranes with different diameters were obtained. The electron microscope images of the PI nanofiber membranes are shown in FIG. Figure 4 shown.
[0045] Example 4: Analysis of filtration performance and mechanical properties of PI nanofiber membranes with different diameters
[0046] (1) Based on the results of Example 3, nanofiber membranes with DMF / acetone ratios of 10:0, 8:2, 7:3 and 6:4 were selected, and their average diameters were 200 nm, 300 nm, 400 nm and 500 nm, respectively, and their filtration performance and mechanical properties were analyzed;
[0047] (2) Filtration performance: The filtration performance of the preferred 200-500 nm PI nanofiber membrane was analyzed by an automatic filtration tester (TSI, USA, Model 8130). The test method was the same as that in Example 2 (1). Among them, the filtration performance of 500 nm was the best, with a filtration efficiency of 94.22%, a resistance of 45.89 Pa, and a quality factor of 0.062 Pa. -1 , the results are as follows Figure 5 As shown;
[0048] (3) Mechanical properties: The preferred 200-500 nm PI nanofiber membrane was subjected to mechanical property analysis using a universal material testing machine. The test method was the same as that in Example 2 (2). Among them, the 500 nm PI nanofiber membrane had the best mechanical properties, with a stress of up to 13.12 MPa. The results are as follows: Figure 6 As shown;
[0049] (4) Based on the analysis of the filtration performance and mechanical properties of the preferred 200-500 nm PI nanofiber membranes, the 500 nm PI nanofiber membrane with the best comprehensive performance was selected, and its DMF / acetone ratio was 6:4.
[0050] Example 5: Preparation of PDMS@PI nanofiber membrane
[0051] In the preferred embodiment 3, the PI nanofiber membrane with DMF / acetone ratio of 6:4 is placed in a closed environment together with a PDMS film, and the temperature is gradually raised to 250°C and maintained for 1 hour. PDMS is decomposed at high temperature and vapor-deposited on the surface of the PI nanofiber during the cooling process to obtain a highly hydrophobic and highly flame-retardant PDMS@PI nanofiber membrane. Its contact angle and flame retardancy are as follows: Figure 7 and Figure 8 shown.
[0052] Example 6
[0053] (1) 1.8 ml of 12 wt% PAA nanofiber membrane with a DMF / acetone ratio of 6:4 was spun, and PI-based nanofiber membrane was obtained after imidization and PDMS vapor deposition;
[0054] (2) The prepared PI-based nanofiber membrane was disinfected and sterilized using three commonly used disinfection methods, and the filtration efficiency, air permeability and water contact angle of each disinfection sample were tested. The selected disinfection methods were alcohol treatment, chlorine-based disinfectant treatment and ultraviolet germicidal irradiation (UVGI). The specific treatment methods are as follows:
[0055] Alcohol treatment: Immerse the sample in 75% ethanol solution, dry it naturally in the air, and test its filtration efficiency. This disinfection-filtration efficiency test also needs to be repeated 5 times
[0056] Chlorine-based disinfectant treatment: Spray about 1% chlorine-based disinfectant on the sample, let it contact with the sample for 30 minutes, then rinse the sample with deionized water and dry it naturally in the air, and test its filtration efficiency. The above disinfection-filtration efficiency test needs to be repeated 5 times to obtain reliable test results.
[0057] UVGI: The samples were placed in a UV disinfection cabinet and irradiated with a 254 nm, 8 W UV lamp for 30 min. The internal area of the UV disinfection cabinet was 475 cm 2 , that is, the unit irradiation power is 17 MW cm-2. After the sample is irradiated, the sample is placed in an air environment for a fixed time of 30 minutes, and then the sample is tested for filtration efficiency. The disinfection-filtration efficiency test also needs to be repeated 5 times;
[0058] (3) After treatment, the filtration efficiency of the PI-based nanofiber membrane remained above 99%. Fig. 9 shown.
[0059] Example 7: Preparation of blended PI nanofiber membrane
[0060] (1) Preparation of spinning solution: ODA was reacted with PMDA and BPDA of equal molar mass in DMF solvent at -5 °C for 12 h to obtain PAA (PMDA-ODA) and PAA (BPDA-ODA) solutions with polymer concentration of ~12 wt%. The two PAA solutions were mixed in different proportions and stirred at low temperature for 12 h to obtain a blended PAA solution.
[0061] (2) Electrospinning: The above blended PAA solution was transferred into a syringe, and the syringe pump pushed the spinning solution. Copper foil was used as the receiving substrate for electrospinning experiments. The spinning solution was controlled to be 0.9 ml, the spinning voltage was 15 KV, the pushing speed was 0.3 ml / h, and the receiving distance was 15 cm.
[0062] (3) Imidization: The prepared blended PAA nanofiber membrane was placed in a box furnace for vacuum gradient heating to 100 °C, 200 °C and 300 °C, respectively. Each temperature gradient was kept for 2 h, and the heating rate was 5 °C / min. After the high temperature treatment, the temperature was naturally cooled to finally obtain a blended PI nanofiber membrane with a polymer concentration of 12 wt%.
[0063] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. An electrospun polyimide (PI)-based nanofiber protective material, the preparation method of which comprises the following steps: S1, using N,N-dimethylformamide (DMF) and acetone in different mass ratios as solvents, dianhydride and diamine monomers are polycondensed to prepare polyamic acid (PAA), wherein the mass ratio of DMF / acetone in the solvent is in the range of 10:0 to 6:4; S2, using the PAA obtained in step S1 as a polymer to prepare a spinning solution, and preparing a PAA nanofiber membrane by electrospinning; S3, thermal imidization of the PAA nanofibers obtained in step S2 to prepare a PI nanofiber membrane; S4, based on step S3, the prepared PI nanofiber membrane and the PDMS film are placed in a closed environment, gradually heated to 250°C, and maintained for 1 hour, PDMS is decomposed at high temperature and vapor-deposited on the surface of the PI nanofiber during the cooling process, thereby obtaining a highly hydrophobic and highly flame-retardant PI nanofiber membrane.
2. The electrospun polyimide (PI)-based nanofiber protective material according to claim 1, characterized in that: The specific operation of step S1 is as follows: dianhydride monomers and diamine monomers of equal molar mass are subjected to low-temperature polycondensation in a DMF / acetone mixed solvent to form a PAA solution, the polycondensation reaction temperature is -5 to 0°C, and the reaction time is 10 to 12 hours; the dianhydride monomer is at least one of pyromellitic anhydride (PMDA), biphenyltetracarboxylic anhydride (BPDA), 4,4'-oxydiphthalic anhydride (OPDA), and 4,4'-hexafluoroisopropylidene-phthalic anhydride (6FDA); the diamine monomer is at least one of 4,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), 2,4,6-trimethyl-1,3-phenylenediamine (TMPDA), and 3,5-diaminobenzoic acid (DABA).
3. The electrospun polyimide (PI)-based nanofiber protective material according to claim 1 or 2, characterized in that: The specific operations of steps S2 and S3 are: the PAA solution is made into a PAA nanofiber membrane through electrostatic spinning technology, and the PAA nanofiber membrane is then subjected to high-temperature imidization to obtain a PI nanofiber membrane; the electrostatic spinning process conditions are a voltage of 10 to 25 KV, a receiving distance of 13 to 18 cm, and an injection speed of 0.2 to 0.8 ml / h; the high-temperature imidization treatment gradient heating process conditions are under vacuum, 100°C for 2 hours, 200°C for 2 hours, 300°C for 2 hours, and a heating rate of 5°C / min. After stopping the heating, it is slowly cooled to room temperature in a box furnace.
4. The electrospun polyimide (PI)-based nanofiber protective material according to claim 1, characterized in that: When the concentration of polymer PAA in step S2 is 14 wt%, the PI nanofiber membrane is composed of alternating thick and thin fibers, with the thick fibers being 200 nm and the thin fibers being 30-40 nm. The thick fibers play a supporting role and the thin fibers play a filtering role.
5. The electrospun polyimide (PI)-based nanofiber protective material according to claim 1, characterized in that: The PI nanofiber protective material has high filtration efficiency>94%, high air permeability>100mm / s, high mechanical strength maximum tensile stress>13MPa, high hydrophobic contact angle>130° and good flame retardancy.
6. The electrospun polyimide (PI)-based nanofiber protective material according to claim 1, characterized in that: The PI nanofiber membrane mainly relies on physical interception, and there is no risk of reduced filtration efficiency due to static elimination. After being treated with 75% alcohol, 1% chlorine-based disinfectant and ultraviolet irradiation and cycled 5 times, the filtration efficiency and hydrophobicity of the PI nanofiber membrane remain unchanged.
7. The electrospun polyimide (PI)-based nanofiber protective material according to claim 1, characterized in that: The prepared PI nanofiber membrane is combined with a substrate by at least one of ultrasound, thermal compounding, and bonding to prepare a reusable medical protective clothing with high air permeability, high mechanical strength, high hydrophobicity, and high flame retardancy.